2022
DOI: 10.3390/s22010403
|View full text |Cite
|
Sign up to set email alerts
|

Motion Capture Sensor-Based Emotion Recognition Using a Bi-Modular Sequential Neural Network

Abstract: Motion capture sensor-based gait emotion recognition is an emerging sub-domain of human emotion recognition. Its applications span a variety of fields including smart home design, border security, robotics, virtual reality, and gaming. In recent years, several deep learning-based approaches have been successful in solving the Gait Emotion Recognition (GER) problem. However, a vast majority of such methods rely on Deep Neural Networks (DNNs) with a significant number of model parameters, which lead to model ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Therefore, the proposed KELM-MFF-based HMR algorithm can be used to deal with large-scale datasets. Bhatia et al ( 2022 ) also have observed that the KELM is suitable for processing large-scale datasets. At present, there are few researches on large-scale dataset processing in sports.…”
Section: Analysis Of Simulation Resultsmentioning
confidence: 98%
“…Therefore, the proposed KELM-MFF-based HMR algorithm can be used to deal with large-scale datasets. Bhatia et al ( 2022 ) also have observed that the KELM is suitable for processing large-scale datasets. At present, there are few researches on large-scale dataset processing in sports.…”
Section: Analysis Of Simulation Resultsmentioning
confidence: 98%
“…According to Figure 12 , HAR is the top-addressed challenge, namely in of the sample. HAR includes recognizing daily performed locomotion modes [ 54 , 55 , 56 , 57 , 153 , 154 ], analyzing the behavior of the elderly in daily life [ 58 , 134 , 135 ], gait analysis [ 59 , 155 , 156 , 157 ], etc. Monitoring is the second most studied issue, namely in of the included papers.…”
Section: Results Analysismentioning
confidence: 99%
“…The micro-average precision (mAP) represents the sum of all true positives divided by the sum of all true positives plus the sum of all false positives. Thus, the number of correctly identified predictions is divided by the total number of predictions [ 58 ].…”
Section: Methodsmentioning
confidence: 99%